Effect of Ultrasound-Treated Arabinoxylans on the Oxidative Stability of Soybean Oil - Mayra A. Mendez-Encinas; Elizabeth Carvajal-Millan; Jesús Ortega-García; Lubitza B. Santiago-Gómez; Yubia De Anda-Flores; Karla G. Martínez-Robinson; Dora E. Valencia-Rivera (MDPI AG, 2020)
Arabinoxylans (AX) are polysaccharides with antioxidant activity and emulsifying properties, which make them an attractive alternative for its potential application as a natural antioxidant in oils. Therefore, this work aimed to investigate the effect of ultrasonic treatment of AX on their antioxidant capacity and its ability to improve the oxidative stability of soybean oil. For this purpose, AX were exposed to ultrasonic treatment at 25% (100 W, AX-1) and 50% (200 W, AX-2) power and an operating frequency of 20 KHz during 15 min, and their macromolecular properties (weight average molecular weight (Mw), polydispersity index and intrinsic viscosity) were evaluated. The antioxidant capacity of AX was determined by the DPPH assay and Rancimat test. Results showed that ultrasonic treatment did not affect the molecular identity of the polysaccharide but modified its Mw distribution. AX-1 showed the highest antioxidant activity (75% inhibition) at 533 µg/mL by the DPPH method compared to AX and AX-2. AX at 0.25% (w/v) and AX-1 at 0.01% (w/v) exerted the highest protective effects on oxidative stability of soybean oil with induction periods of 7.69 and 5.54 h, respectively. The results indicate that AX could be a good alternative for the potential application as a natural antioxidant in oils.